Hatice Gonnet Bağana Anatolian Civilizations and Hittite Digital Collection - Maner, Çiğdem; Acar, Senem; Soğuksu, Derya; Akbaytürk, Tuba (Information World, 2016)
In 2014 Hittitologist Prof. Dr. Hatice Gonnet Bağana, a resident of Paris, donated her library, archive and visual collections to Koç University’s Suna Kıraç Library. Gonnet Bağana, who was a student of Professor Emmanuel Laroche in Paris, was elected as the Hittitologist in charge at Ecole Pratique des Hautes Etudes V. Section, after Emmanuel Laroche’s retirement. Gonnet Bağana’s archive contains monographs, offprints, translations and transcriptions of Hittite texts, manuscripts, images from excavation sites, maps, and plans. This article discusses this collection from its donation to Koç University to its acquisation process and shipment from Paris to Istanbul, and from its classification, physical process and storage to digitization in the library. What makes this collection and digitization project unique is its specialization in Hittitology as being the first personal Hittiology archive digitized to be accessible for the researchers across the globe.
Keywords: Hittitology; archaeology collection; digitization; digital collection; archiving practice; academic libraries